Plasmonic characteristics of magnetized plasma–graphene-magnetized plasma–perfect magnetic conductor planar waveguides - Umair M.; Ghaffar Abdul; Alkanhal Majeed A.S.; Khan Yasin; Shahid M.U.; Ali M. Amir (Journal of the European Optical Society-Rapid Publications, 2025)
This manuscript explores the novel characteristics of surface plasmon polaritons (SPPs) in the terahertz (THz) frequency region by numerically investigating the magnetized plasma–graphene-magnetized plasma–perfect magnetic conductor (PMC) planar interface. Substrates are assumed to be PMCs. The dispersion equations for the field components are derived, and the Kubo formula is utilized for the physical modeling of graphene conductivity. The numerical results show that the plots of effective mode index, propagation length, and phase velocity can be varied by adjusting the chemical potential, number of graphene layers, and tensorial permittivity parameters of the magnetized plasma medium (i.e., plasma frequency and cyclotron frequency). Furthermore, the cutoff frequency for the proposed waveguide structure is analyzed.